119k views
2 votes
In the equation 6x − 2 = −4x + 2, Spencer claims that the first step is to add 4x to both sides. Jeremiah claims that the first step is to subtract 6x from both sides. Who is correct?

User Sineverba
by
6.0k points

2 Answers

3 votes

Answer: Both Technically, Look Below

Explanation:

This is a very interesting problem they are technically both not wrong. You can choose to subtract the 6x first if you want or add 4x. Both technically work and will end up with the same value for x. Which I will show here. Although both work adding 4x can be the easier way as there is less negatives to deal with.

Adding 4x:

6x - 2 = -4x + 2

10x - 2 = 2

10x = 4

x = 4/10

x = 2/5

Subtraction 6x:

6x - 2 = -4x + 2

-2 = -10x +2

-4 = -10x

4/10 = x

2/10 = x

User Surie
by
5.6k points
3 votes

Answer:

Both are correct in their order of steps. In does not matter which you subtract or add as long as you are eliminating something from each side. However, in order to keep the equation positive, the most preferred step would be to add 4x.

User Hasibur Rahman
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.